TEORES DE LIPÍDIOS TOTAIS, ÁCIDOS GRAXOS E COLESTEROL EM RESÍDUOS DESIDRATADOS DE CAMARÃO-SETE-BARBAS ( Xiphopenaeus kroyeri, HELLER 1862) CAPTURADO NO ESTADO DO RIO DE JANEIRO - FREITAS, ARLAN SILVA; BORGES, JOÃO TOMAZ DA SILVA; COSTA, ROZENNE KERLEY; CORNEJO, FÉLIX EMÍLIO PRADO; WILBERG, VIKTOR CHRISTIAN (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2002)
Efetuou-se estudo sobre os lipídios totais, ácidos graxos e colesterol presentes resíduos desidratados de camarão, visando o aproveitamento total do crustáceo na alimentação humana. Resíduos de camarão-sete-barbas (cefalotórax, segmentos abdominais e caudas) foram lavados com água clorada, cozidos, desidratados, moídos e o produto final analisado. O teor de lipídios totais encontrado foi de 2,66% e o de colesterol de 98,82 mg/100 g. Do total dos ácidos graxos 34,43% corresponderam aos ácidos graxos saturados, 30,30% aos monoinsaturados e 35,26% aos polinsaturados. Os resíduos desidratados de camarão podem ser destinados à alimentação humana como flavorizante natural, conferindo sabor e aroma característicos ao alimento. LEVELS OF TOTAL LIPIDS, CHOLESTEROL AND FATTY ACIDS IN THE DEHYDRATED RESIDUES OF THE SEVEN-BEARDS-SHRIMP (Xiphopenaeus kroyeri, HELLER 1862) CAPTURED IN THE STATE OF RIO DE JANEIRO Abstract The production of shrimps in Brazil grew significantly in the last years and with excellent conditions for expansion. Although it is appreciated in the cookery, the shrimp is considered a food of high cholesterol tenor. The shrimp residues, when submitted appropriately to the cooking process, following by dehydration and reduction of particles can be destined to the human feeding as a natural flavor substance, checking to the food, flavor and aroma characteristic of shrimp. Occurred study on the total lipids, fatty acids and cholesterol, presents in total use of the crustacean in the human feeding. Residues of seven-beards-shrimp (cephalotorax, abdominal segments and tails) were washed with chlorinated water, cooked, dehydrated and grinded. In the obtained product the levels of total lipids, cholesterol and fatty acids were determinated. The total lipids and cholesterol contents were 2,66% and 98,82 mg/100g. From the total of the fatty acids 34,43% corresponded to the saturated, 30,30% to the monoinsatured and 35,26% to the polinsatured fatty acids.